White lighting and colour preference, Part 1: Correlation analysis and metrics validation. (January 2020) - Huang, Z; Liu, Q; Pointer, MR; Luo, MR; Wu, B; Liu, A
In this work, the correlation between the whiteness of lighting and the preference for the colour of lighting was comprehensively investigated based on four psychophysical studies. Different sets of experimental light sources, two of constant correlated colour temperatures (CCT) and two of different CCTs were adopted to illuminate multiple experimental objects with different illuminance levels (200 lx or 500 lx). The observers were asked to rate their colour preference towards the illuminated objects and rate their white perception towards the illuminated environment of the empty light booth. It was found that for the studies with same CCT but different chromaticities, people indeed preferred whiter illumination. However, for the cases with multiple CCTs, that statement is only valid between 2500 K and 5500 K, since too white a light source impaired colour preference. In addition, based on the whiteness rating data, the performance of three typical metrics for white lighting was assessed. The findings of this study may contribute to a deeper understanding of colour and whiteness perception in lighting, especially for lighting designers and manufacturers.